Migration Inhibitory Factor in Conditioned Medium from Human Umbilical Cord Blood-Derived Mesenchymal Stromal Cells Stimulates Hair Growth - Hyun Ah Oh; Jihye Kwak; Beom Joon Kim; Hye Jin Jin; Won Seok Park; Soo Jin Choi; Wonil Oh; Soyoun Um (Cells, 2020)
Conventional therapeutic applications of mesenchymal stromal cells (MSCs) focus on cell replacement and differentiation; however, increasing evidence suggests that most of their therapeutic effects are carried out by their various secretions. This study investigated the application of conditioned medium (CM) from human umbilical cord blood-derived MSCs (hUCB-MSCs) to improve hair growth and developed a method to reliably produce this optimized CM. Primed MSC-derived CM (P-CM) with combinations of TGF-β1 and LiCl was optimized by comparing its effects on the cell viability of dermal papilla cells (DPCs). P-CM significantly increased the viability of DPCs compared to CM. The secretion of vascular endothelial growth factor (VEGF) in DPCs was regulated by the macrophage migration inhibitory factor (MIF) in the P-CM secreted by MSCs. These findings suggest that P-CM can improve the efficacy in hair growth via a paracrine mechanism and that MIF in P-CM exerts hair growth-promoting effects via a VEGF-related β-catenin and p-GSK-3β [SER9] signaling pathway. Furthermore, clinical trials have shown that 5% P-CM improved androgenetic alopecia through producing an increased hair density, thickness, and growth rate, suggesting that this topical agent may be a novel and effective treatment option for patients with androgenetic alopecia.